2002
DOI: 10.1034/j.1600-6143.2002.20311.x
|View full text |Cite
|
Sign up to set email alerts
|

First Clinical Use of a Novel Bioartificial Liver Support System (BLSS)

Abstract: The first clinical use of the Excorp Medical Bioartificial Liver Support System (BLSS) in support of a 41-year-old African-American female with fulminant hepatic failure is described. The BLSS is currently in a Phase I/II safety evaluation at the University of Pittsburgh/UPMC System. Inclusion criteria for the study are patients with acute liver failure, any etiology, presenting with encephalopathy deteriorating beyond Parson's Grade 2. The BLSS consists of a blood pump; a heat exchanger to control blood tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(47 citation statements)
references
References 11 publications
0
43
0
4
Order By: Relevance
“…Система MELS, разработанная в клинике Charite Virchow (Берлин, Германия) состоит из биореактора (CellModule) с гепатоцитами свиней или человека, детоксикационного блока (DetoxModule) на основе альбуминового диализа и диализного модуля (DialysisModule) для осуществления длительной вено-венозной гемодиафильтрации [87,121,122]. Гепатоциты (500-600 г) фиксируются в 3D матриксе, состоящем из двух групп гидрофильного материала для транспорта плазмы и группы гидрофобных волокон для поставки кислорода и удаления углекислого газа.…”
Section: аппарат Mels (Modular Extracorporeal Liver Support)unclassified
“…Система MELS, разработанная в клинике Charite Virchow (Берлин, Германия) состоит из биореактора (CellModule) с гепатоцитами свиней или человека, детоксикационного блока (DetoxModule) на основе альбуминового диализа и диализного модуля (DialysisModule) для осуществления длительной вено-венозной гемодиафильтрации [87,121,122]. Гепатоциты (500-600 г) фиксируются в 3D матриксе, состоящем из двух групп гидрофильного материала для транспорта плазмы и группы гидрофобных волокон для поставки кислорода и удаления углекислого газа.…”
Section: аппарат Mels (Modular Extracorporeal Liver Support)unclassified
“…Zwei Zentren haben das HepatAssist-System zum Bridging bis zur Transplantation eingesetzt [63,64].Die von Demetriou in Los Angeles entwickelte Bioartificial Liver (BAL) trug bei 16 von 17 Patienten zum erfolgreichen Bridging bis zur Lebertransplantation bei [65]. Aus Pittsburgh wurde über einen positiven Einsatz des Bioartificial Liver Support System (BLSS) an einem Patienten berichtet [66]. …”
Section: Hepatassist Bal Blssunclassified
“…The first case of treatment with BLSS is a 4l-yearold female patient with ALF. 155 After treatment, the patient had the concentrations of ammonia, lactate, and total bilirubin decreased, coagulation function and clinical symptoms improved, and eventually removed off the BLSS treatment. There was another study that reported four cases with ALF treated with BLSS.…”
Section: Excorp Medical Bioartificial Liver Support Systemmentioning
confidence: 99%